2021
DOI: 10.1177/01492063211011762
|View full text |Cite
|
Sign up to set email alerts
|

Strategic Risk and Lobbying: Investigating Lobbying Breadth as Risk Management

Abstract: Despite many studies investigating how lobbying expenditures enhance performance outcomes, limited attention has been given to understanding the underlying mechanisms driving firm lobbying behaviors—and, particularly, where firms target their lobbying expenditures. We argue lobbying breadth serves as a risk management strategy to both hedge against possible government intrusion and minimize disapproval of firm actions from government officials. As such, we posit firms’ strategic risk will positively relate to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 133 publications
(191 reference statements)
1
12
0
Order By: Relevance
“…Favorable internal and external characteristics will decrease a firm’s political transaction costs. While the environment might influence how firms engage in CPA (Brown, Manegold, & Marquardt, 2020), government risks have been found to be especially important in influencing firm CPA (Abdurakhmonov et al, 2021). When government risks are perceived to be high, through public political risk and home government relations, firms will attempt to evade risk with the host government (De Villa, Rajwani, Lawton & Mellahi, 2019).…”
Section: Predictors Of Cpamentioning
confidence: 99%
See 1 more Smart Citation
“…Favorable internal and external characteristics will decrease a firm’s political transaction costs. While the environment might influence how firms engage in CPA (Brown, Manegold, & Marquardt, 2020), government risks have been found to be especially important in influencing firm CPA (Abdurakhmonov et al, 2021). When government risks are perceived to be high, through public political risk and home government relations, firms will attempt to evade risk with the host government (De Villa, Rajwani, Lawton & Mellahi, 2019).…”
Section: Predictors Of Cpamentioning
confidence: 99%
“…At this point, it appears that researchers have not taken full advantage of this publicly available data, although there are some notable exceptions. Abdurakhmonov et al, (2021), for example, investigated where firms target their lobbying expenditures. They found that broadly lobbying across various lobbying agencies and legislative acts can mitigate political risks.…”
Section: The Variety Of Cpa Approachesmentioning
confidence: 99%
“…Although organizations engage in political activities (e.g. donations, lobbying; Abdurakhmonov et al, 2021) to promote their interests, the political activities of managers constitute an embodiment of their personal beliefs and values (Burris, 2001). Consequently, it can be inferred that the political ideology of a CEO is distinct from the political orientation of the organization.…”
Section: Political Ideologymentioning
confidence: 99%
“…Although organizations engage in political activities (e.g. donations, lobbying; Abdurakhmonov et al. , 2021) to promote their interests, the political activities of managers constitute an embodiment of their personal beliefs and values (Burris, 2001).…”
Section: Ceos' Political Ideology and Work–family Policiesmentioning
confidence: 99%
“…The breadth of a firm's lobbying reflects "the extent of government activities or entities the firm is attempting to influence," while the depth of its lobbying is "concentrated on a limited number of relationships that can be exploited" (Ridge et al, 2017(Ridge et al, , pp.1139(Ridge et al, , 1146. Although researchers are paying increased attention to lobbying breadth and depth (Abdurakhmonov et al, 2021), Ridge et al (2017Ridge et al ( , p.1158 highlight that "there is much opportunity for future research to further develop and examine these dimensions" of lobbying. Drawing on theories of social capital, we inquire into the breadth and depth of insider lobbying by investigating the extent and number of direct meetings that firms hold with key political actors and the value of the contracts awarded to companies by the UK's Ministry of Defence (MOD), along with the moderating effects of firm size on that relationship.…”
Section: Introductionmentioning
confidence: 99%